Peripety in an R&D drama: capturing a turnaround in project dynamics - Engwale, Mats; Nestling, Gunnar (2004)
This article examines the process dynamics of a complex R&D project, which for a long period of time had suffered from little technical progress, then abruptly became highly structured and effective. The article examines the mechanisms behind this dramatic turnaround and discusses its implications for research and practice. Drawing on the dramaturgical concept of `peripety' (`moment of sudden change'), the article captures how the turnaround came about due to the emergence of the participants' shared conceptualization of the project mission. The article provides insights into the process dynamics and sensemaking in complex R&D projects and demonstrates how time and evolution need to be included in the analysis of project management and temporary organizations. - Reproduced.
Keywords: Research and development; Project management